Postprandial platelet-poor plasma 5-hydroxytryptamine concentrations during diarrhea and constipation periods of alternatingtype irritable bowel syndrome patients - Fatma ŞEN; Binnur PINARBAŞI; Halim İŞSEVER and Filiz AKYÜZ and Zeynel MUNGAN and Sabahattin KAYMAKOĞLU (Turkish Journal of Gastroenterology, 2019)
-